Improved design method for the nuclear island periodic raft-pile foundation hybrid isolation system considering soil structure interaction - Jianbo Li; Hongwei Hou; Zhiyuan Li; Gao Lin; Jinhong Luo (Computers and Geotechnics, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Microplastics from catchment to offshore: Salinity gradients and seasonal discharge control estuarine trapping efficiency and tidal reimport - Kazi Belayet Hossain; Junge Wang; Yang Zhou; Xiangrong Xu; Lang Lin; Xiaoshan Zhu; Yang Liu; Bin Chen; Hongwei Ke; Minggang Cai (Water Research, 2026)

ABA-dependent priming of stomatal immunity by the harpin protein PopW restricts entry of Xanthomonas euvesicatoria in tomato - Xiaosi Zhou; Tian Wei; Yuwei Xue; Jiangfei Hu; Yuqing Lin; Lina Xu; Hongwei Zhao; Hongxia Liu (Plant Science, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

S100 signaling in hair follicle biology: emerging mechanistic insights and therapeutic opportunities - Dongfan Wei; Hongwei Jia; Lin Shang; Di Zhang; Fenglin Zhuo (Journal of Molecular Histology, 2026)

Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Predictive gas recirculation control for CO2-modified atmosphere treatment in a full-scale concrete maize silo using conditional multi-step forecasting - Jie Lin; Kun Hu; Xiaoping Yan; Haoyu Wen; Xiaoyu Zhang; Yining Wu; Yuanyi Luo; Hongwei Xiao (Journal of Stored Products Research, 2026)

Optimized design of the bulge structure for alkaline electrolyzers based on response surface methodology - Jianqing Lin; Xiaoyang Ma; Jiayi Li; Hongwei Li; Tieliu Jiang; Kaichen Wang; Zhirong Liao; Chao Xu; Gang Wang (Journal of Cleaner Production, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Settling by water: Human habitation adapted to landscape evolution at the Xuecheng site in the lower reaches of the Yangtze River during the Mid-late Holocene - Zhiping Zhang; Zhujun Hu; Xingyu Zhou; Hui Peng; Jue Sun; Jiahao Xu; Hongwei Shi; Lin Yang; Ping Zhang; Feng Xu; Harry F. Lee; Xin Jia (Science China Earth Sciences, 2026)

The maize CMS-C fertility restore gene ZmRf4b encodes a SPL transcription factor that represses ZmMAP1D-mediated co-translational turnover of mitochondrial toxic ATP6C protein - Bing Li; Huaisheng Zhang; Runbo Zhang; Shicheng Feng; Fanli Yang; Congnian Ding; Xuyuan Shen; Keke Shao; Lu Yang; Yanan Lin; Dong Ding; Quancan Hou; et al. (Molecular Plant, 2026)

From natural extraction to heterologous biosynthesis: The evolution of preparation strategies for bioactive compounds from medicinal plants - Jing Guan; Hongyuan Luo; Hongwei Li; Lin Li; Weie Wen; Delin Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Cooperative LoRA with frequency priors for SAM2-Based multimodal remote sensing semantic segmentation - Hongwei Tong; Jingyan Huang; Lin Chai (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Electrochemical engineering in situ induces highly thermodynamically stable interface toward long-life zinc metal anodes - Min Lin; Le Zhang; Xijun Liu; Shuyu Bi; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

Erratum to “Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface” [Bioresour. Technol. 451 (2026) 134559] - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

A novel AgNPs spongy trap coupled with portable XRF: a field-ready strategy for sensitive mercury analysis in soils - Lin Li; Yan Xu; Guanyu Lan; Zhenzhen Yao; Xiaoqin Chen; Mengyu Liu; Hongwei Shi; Xue Li; Xuefei Mao (Analytica Chimica Acta, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

Lignin-based porous materials with balanced strength-toughness for highly efficient oil-water separation - Hongwei Yu; Tao Lin; Xinyi Zheng; Jingda Huang; Wenbiao Zhang; Weimiao Lu (Process Safety and Environmental Protection, 2026)

Identifier-critic-based distributed optimal consensus control of USVs with guaranteed performance - Lin Chen; Yaonan Wang; Xudong Wang; Hongwei He; Baoyuan Deng (Ocean Engineering, 2026)

TomOmics: An integrative multi-omics platform for comparative and functional research in tomato - Yan Wang; Tailai Yang; Yuru Song; Qinqin Yang; Xiao Su; Hongwei Li; Yushan Li; Ming Zhou; Tao Lin (Molecular Plant, 2026)

Forecasting groundwater nitrate vulnerability dynamics through spatiotemporal lagged bivariate local indicators of spatial association: Linking self-past to neighborhood-future states - Yonggang Li; Xiaojing Hu; Xu Guo; Lin Gao; Xiaoqing Song; Hongwei Liu; Chuanming Ma (Environmental Research, 2026)

Response of soil humic substances to snowpack decline across different soil layers in the subalpine forest - Li Zhang; Wenlan Huang; Yao Liu; Sining Liu; Han Li; Bo Tan; Chengming You; Hongwei Xu; Lin Xu; Zhenfeng Xu; Yalin Yuan; Jiao Li; et al. (CATENA, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Photocatalytic hydrogen production: Materials design, system engineering, and data-driven advances - Gengran Zhai; Junchen Liu; Shiyi Lin; Yifan Cheng; Bin Wang; Qingyao Jiang; Hongwei Fu; Hongxin Zhao; Yuan Lu (Chemical Engineering Journal, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Efficient roxarsone degradation via in-situ H2O2 generation through 2e−ORR over a Pd-Fe2O3 catalyst system - Ruibin Yang; Shuang Yao; Yijun Chen; Zhiwen Jiang; Hangyu Zhang; Ke Wang; Dapeng Li; Feng Liu; Feiyue Qian; Hailiang Yang; Sanjian Ma; Zixia Lin; et al. (Journal of Environmental Management, 2026)

Label-efficient outdoor 3D object detection via single click annotation from LiDAR point cloud - Qiming Xia; Hongwei Lin; Wei Ye; Yadan Luo; Shijia Zhao; Hai Wu; Chenglu Wen; Cheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Seasonal comparison of primary productivity and microeukaryotic plankton community structure between two seagrass bed ecosystems in northern and southern China - Zhexuan Shi; Ziqi Liu; Jiahong Zhu; Zhi'en Liu; Hongwei Wang; Siyang Wu; Luyao Chen; Weifang Chen; Xin Lin (Estuarine, Coastal and Shelf Science, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Assessing CO2-Modified atmosphere fumigation in a concrete maize silo for feasibility, gas distribution, and insect control efficacy - Jie Lin; Yuanyi Luo; Shuanglin Wang; Xiaoping Yan; Kun Hu; Hongwei Xiao (Journal of Stored Products Research, 2026)

Patterns and drivers of plant- and microbial-derived carbon in a cedar plantation chronosequence of subtropical China - Yuehan Wang; Yu Li; Chengming You; Hongwei Xu; Han Li; Lin Xu; Li Zhang; Lixia Wang; Sining Liu; Bo Tan; Yaling Yuan; Jiao Li; et al. (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Acidification and deoxygenation matter in assessing redistribution of global cold‐water coral biodiversity induced by climate change - Shuaishuai Liu; Bingqing Xiao; Ákos Bede‐Fazekas; Stefano Mammola; Jorge García Molinos; Jamie M. Kass; Jorge Assis; Chen Lin; Junmei Qu; Hongwei Huang; Qiang Lin; Zhixin Zhang (Limnology and Oceanography, 2026)
The ocean is undergoing significant changes, including warming, acidification, and deoxygenation, which pose great challenges to marine biodiversity. However, most models projecting the impacts of climate change on marine species overlook predictor variables critically meaningful for species' ecologies such as pH and dissolved oxygen. The recent release of high‐resolution projections of different future climate‐change scenarios offers the opportunity to explore species redistribution under multiple threats beyond ocean warming. Accordingly, we conducted a global comparative analysis to study the impact of incorporating predictor variables describing pH and dissolved oxygen into marine species distribution models. We used models trained for 268 cold‐water coral species to project potential future distributions for different climate and dispersal scenarios over different time periods. We found that, irrespective of scenario or period, models using pH and dissolved oxygen projected 11.5–21.4% higher impacts of climate change than those without them. For instance, by the end of the century under a high emission scenario, models including pH and oxygen projected an average range contraction of 48.2% for cold‐water corals under a no‐dispersal scenario, compared with a 26.8% contraction projected by models excluding these two predictors. Given the substantial differences in the predicted distribution patterns and the biological importance of these variables, we highlight that researchers should consider more diverse sets of predictor variables when predicting future range shifts for marine biodiversity assessments under climate change.

FSHR-GnRH bispecific vaccine suppresses the fertility of female rats - Jingjing Zhang; Xinyue Jiang; Yuke Jia; Jingya Xu; Yuwen Huang; Tao Tao; Meng Cao; Wei Qian; Fugui Fang; Yunsheng Li; Yinghui Lin; Hongwei Duan; et al. (Theriogenology, 2026)

Spatiotemporal evolution and dissipation mechanisms of tidal current turbine wake under different turbulence intensities - Tian Zou; Yajing Gu; Hongwei Liu; Zhiwei Song; Hongyi Lin; Yuquan Zhang (Ocean Engineering, 2026)

Dual mechanisms of mineral-microbial interactions in suppressing organic carbon sequestration in calcareous soils - Xi Yang; Donghao Ma; Ting Yang; Yongqi Zhang; Lin Chen; Hongwei Jiang; Bingru Chen; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; et al. (Journal of Environmental Management, 2026)

Flexible multi-parameter sensing platform using MoWS2-BP composite for environmental and physiological monitoring - Yu Qi; Long Yang; Zitong Kan; Qingqing Zhou; Biao Dong; Guodong Wei; Hongwei Song; Lin Xu (Chemical Engineering Journal, 2026)

Polyamide microplastic pollution modifies the sediment fungal structures associated with different submerged plant species: An insight from aquatic mesocosm experiment - Tong Wang; Jingwen Zhang; Xue Yang; Yinuo Zhu; Lin Qi; Mingyan Li; Xiao Guo; Hongwei Yu; Haifang Li (Applied Soil Ecology, 2026)

Design of a High-Fidelity Motion Data Generator for Unmanned Underwater Vehicles - Li Lin; Hongwei Bian; Rongying Wang; Wenxuan Yang; Hui Li (Journal of Marine Science and Engineering, 2026)
To address the urgent need for high-fidelity motion data for validating navigation algorithms for Unmanned Underwater Vehicles (UUVs), this paper proposes a data generation method based on a parametric motion model. First, based on the principles of rigid body dynamics and fluid mechanics, a decoupled six-degrees-of-freedom (6-DOF) Linear and Angular Acceleration Vector (LAAV) model is constructed, establishing a dynamic mapping relationship between the rudder angle and speed setting commands and motion acceleration. Second, a segmentation–identification framework is proposed for three-dimensional trajectory segmentation, integrating Gaussian Process Regression and Ordering Points To Identify the Clustering Structure (GPR-OPTICS), along with a Dynamic Immune Genetic Algorithm (DIGA). This framework utilizes real vessel data to achieve motion segment clustering and parameter identification, completing the construction of the LAAV model. On this basis, by introducing sensor error models, highly credible Inertial Measurement Unit (IMU) data are generated, and a complete attitude, velocity, and position (AVP) motion sequence is obtained through an inertial navigation solution. Experiments demonstrate that the AVP data generated by our method achieve over 88% reliability compared with the real vessel dataset. Furthermore, the proposed method outperforms the PSINS toolbox in both the reliability and accuracy of all motion parameters. These results validate the effectiveness and superiority of our proposed method, which provides a high-fidelity data benchmark for research on underwater navigation algorithms.

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

CFD data-driven CNN-LSTM for fast prediction of instantaneous flow characteristics in hydrocyclones - Dianyu E; Yuhao Zhang; Hongwei Hu; Guangtai Xu; Lin Liu; Jiaxin Cui; Cong Tan; Ruiping Zou; Shibo Kuang (Minerals Engineering, 2026)

Stage-specific neurotoxicity of lead in zebrafish: Metabolic disruption in embryos and ferroptosis in larvae - Jian Liu; Guizhen Yan; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2026)

Regulatory mechanisms underlying stress-induced accumulation of plant secondary metabolites - Sujing He; Jiangna Wang; Ning Yang; Hongwei Li; Kunqian Li; Lin Li; Wei’e Wen; Tingting Luo; Juanjuan Zhao; Delin Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Quantitative proteomics analysis to identify potential biomarkers associated with promoted quality profiles of frankfurters by ultrasound treatment combined with κ-carrageenan - Shiwen Lin; Zhigang Sun; Yutong Liu; Chuanai Cao; Baohua Kong; Hongwei Zhang; Qian Liu (Food Chemistry, 2026)

Crab bioturbation enhanced sediment nitrogen retention and weakened N2O production in saline-alkaline paddies - Xinru Zeng; Xianbiao Lin; Can Wang; Hongwei Shan; Chuang Sun; Fang Wang (CATENA, 2026)

Using statistical Change-Point Analysis to refine Holocene estuarine–deltaic transition - Penghui Lin; Guanjun Xu; Xianhe Zhang; Fang Li; Xiaolin Xu; Hongwei Li; Zhongping Lai (CATENA, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Changes in litter chemical properties mediate the effects of soil arthropods on the microbial community during litter decomposition in a subalpine forest - Aomiao Wu; Jingru Liu; Rui Yin; Lin Xu; Chengming You; Zhenfeng Xu; Li Zhang; Han Li; Lixia Wang; Sining Liu; Hongwei Xu; Bo Tan (Applied Soil Ecology, 2026)

Effects of Deep Learning Bias Correction and Carbon Neutrality on Projections of Future Population Exposure to Extreme Precipitation - Xiaohua Xiang; Wenbin Wang; Xiaoling Wu; Zhu Liu; Adnan Rajib; Lei Wu; Hongwei Cao; Xian Lin; Yuan Liu (International Journal of Climatology, 2026)
Spatiotemporal variations in extreme precipitation and their impacts on population exposure remain poorly understood due to biases in climate model projections and assumptions inherent in emission scenarios. In this study, we evaluate the bias‐correction performance of three deep learning techniques—Convolutional Neural Networks (CNN), Long Short‐Term Memory networks (LSTM), and hybrid CNN‐LSTM—using extreme precipitation indices derived from 10 Coupled Model Intercomparison Project Phase 6 (CMIP6) models. Building on this, we assess exposure for China's nine river basins under Shared Socioeconomic Pathway (SSP)1–2.6 and SSP3–7.0 in the near future (2031–2060) and far future (2071–2100) and quantify the potential benefits of achieving carbon neutrality on reducing population exposure to extreme precipitation. Our findings reveal that CNN outperforms both LSTM and CNN‐LSTM in correcting biases. Compared to the historical period (1985–2014), both R95p and Rx1day exhibit increasing trends across China at the scenario and temporal levels. The SSP3–7.0 scenario shows more pronounced increases than SSP1–2.6, and the long‐term trends (2071–2100) are greater than those observed in the short‐term period (2031–2060). Spatially, the strongest responses are observed in the southwest and southeast coastal regions, while changes in inland areas are more moderate. On the exposure side, SSP3–7.0 results in a substantial national increase, with far‐future exposure projected to reach approximately 2.7 times the near‐future levels for Rx1day and 1.2 times for R95p. Hotspot areas of exposure are found along the Yangtze–Pearl River Delta–Southeast coastal belt, the southwestern uplands, and the Beijing–Tianjin–Hebei–Bohai corridor. In contrast, the carbon‐neutral pathway (SSP1–2.6) leads to approximately 80% reductions in national exposure in the far future, with reductions greater than 70% in all nine basins. We suggest that climate extreme changes, rather than population dynamics or extreme‐population interactions, are anticipated to dominate these reductions in the future. These results provide important scientific support for ongoing efforts aimed at achieving carbon neutrality by the 2060s to reduce the potential risk of extreme precipitation in China and its nine major river basins.

Multi-objective optimization of a semi-submersible floating wind Platform: Integrating cost, stability, and strength - Siqi Lai; Hongwei Liu; Yajing Gu; Rongfu Li; Long Fang; Yonggang Lin; Souleymane Drabo; Xiangheng Feng (Ocean Engineering, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Enhanced degradation of sulfamethazine by Achromobacter via oxygenation through co-metabolism - Luping Zeng; Xianke Lin; Hongwei Du; Huaiyang Fang; Xiuqin Tan; Bangjie Huang; Yang Yang; Ran Tao (Journal of Environmental Management, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

Hydrodynamic forces on small-diameter pipelines in combined wave-and-current flows - Yunfei Teng; Terry Griffiths; Hongwei An; Scott Draper; Liang Cheng; Henning Mohr; Cheng Zhang; Guoqiang Tang; Lin Lu (Coastal Engineering, 2025)

A novel and robust Fourier-based Kolmogorov-Arnold Network in early warning of rockbursts from microseismic data - Hongwei Guo; Lele Zheng; Shan Lin; Miao Dong; Xitailang Cao; Hong Zheng (Stochastic Environmental Research and Risk Assessment, 2025)

Early Cenozoic source to sink relation between the Tula Basin and the surrounding ranges: Insights for the Tibetan Plateau growth - Jingzhen Peng; Feng Cheng; Dehai Zhang; Hongwei Zhou; Maomao Wang; Xiangzhong Li; Zhaojie Guo; A. K. Khudoley; A. S. Tesakov; Lin Wang; Yan Ma (Science China Earth Sciences, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

Competitive blockade of NKCC1 by potassium suppresses thallium bioaccumulation and neurotoxicity in zebrafish: Implications for aquatic toxicity - Jian Liu; Xin Li; Yiwen Zhu; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Science of The Total Environment, 2025)

Research on an electro-hydraulic individual pitch system of tidal current turbine - Pengpeng Zhang; Hongwei Liu; Yajing Gu; Liyan Lou; Yonggang Lin; Rongfu Li; Qingjun Li; Luoyang Huang; Jianzhong Tang (Ocean Engineering, 2025)

Peptidomics and molecular docking reveal digestion-resistant IgE-binding epitopes in bovine β-lactoglobulin and α-lactalbumin from simulated infant digestion - Fan Yang; Hongwei Zhang; Shaolei Wang; Xue Zhao; Yuying Tang; Jianhua Zeng; Weixue Zhao; Shuo Feng; Changhong Ma; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

The reverse osmosis desalination system driven by the marine current turbine under dynamic conditions - Yajing Gu; Tian Zou; He Ren; Hongwei Liu; Yonggang Lin; Zhiwei Song; Kenan Ye (Desalination, 2025)

Activation of peroxymonosulfate by magnesium−modified biochar for the degradation of imidacloprid: Effectiveness and mechanisms - Xianguo Ji; Hao Lin; Yan Zhang; Jianbo Lu; Yanxiang Zhang; Hongwei Sun; Gang Wang; Xiaoyong Yang; Wei Li; Jinming Duan; Yucan Liu (Chemical Engineering Journal, 2025)

Analysis of the gut-specific microbiome from critically endangered hawksbill sea turtles (Eretmochelys imbricata) using a culture-dependent approach - Hongwei Li; Yuan Chen; Zhongrong Xia; Yunyong Lin; Ruijun Xu (Frontiers in Marine Science, 2025)
Introduction The critically endangered hawksbill turtle (Eretmochelys imbricata) is essential for healthy coral reef ecosystems, and its gut microbiota plays a vital role in host nutrition and overall health. A comprehensive understanding of this microbial diversity is crucial for effective conservation, yet current knowledge remains limited. This study aimed to characterize the bacterial taxa present in the fecal samples of hawksbill turtles using culture-dependent methods. Methods Fecal samples from hawksbill turtles were cultured under both aerobic and anaerobic conditions using two distinct bacterial media. A total of 161 bacterial strains were isolated and identified using standard microbiological techniques and 16S rRNA gene sequencing. Results The isolated strains were classified into three phyla: Pseudomonadota (formerly Proteobacteria), Actinomycetota, and Bacillota (formerly Firmicutes). The most frequently identified species were Psychrobacter celer, Shewanella algae, Sulfitobacter pontiacus, Vibrio mytili, Enterococcus hirae , and Psychrobacter maritimus . Ten isolates were identified as potentially representing six novel bacterial species. Discussion This study expands our understanding of the microbial diversity associated with hawksbill turtles. It demonstrates the utility of fast and simple culture-dependent approaches for characterizing the microbiota of endangered species, providing a foundation for future research into the roles of these bacteria in turtle health and reef ecosystem function.

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Mitigation of greenhouse gas emissions and nitrogen losses caused by migration and tourism in China's tropical island cities - Xiaoyang Shan; Zhaohai Bai; Lin Ma; Shuqing Zhao; Hongwei Zhao (Journal of Environmental Management, 2025)

Innovative strategy for determining the spatial decoupling high-precision artificial boundary range under soil structure interaction - Hongwei Hou; Jianbo Li; Zhiyuan Li; Gao Lin (Computers and Geotechnics, 2025)

Sedimentary Structure Characteristics and Spatial Distribution Pattern of the Zhaoji Salt Mine Derived from Dense Array Ambient Noise Tomography - Hongwei Wang; Xiaofeng Tian; Qiaoxia Liu; Jia Cheng; Ming Zhou; Zhiping Xu; Jiyan Lin; Shuaipeng Zhu (Journal of Earth Science, 2025)

A three-dimensional Pt@Ti₃C₂Tₓ-based smart platform for discrimination of hydrated ammonia in multi‐scenario environmental monitoring - Qingqing Zhou; Chencheng Hu; Yu Qi; Xiaoyi Tan; Jiaqi Yang; Zitong Kan; Long Yang; Biao Dong; Zhiyong Chang; Hongwei Song; Lin Xu (Journal of Hazardous Materials, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Liquid metal modified all-nanofiber triboelectric nanogenerator for energy harvesting and multi-functional self-powered sensing - Long Yang; Wenbo Hu; Ruida Cao; Qingqing Zhou; Chencheng Hu; Biao Dong; Hongwei Song; Lin Xu (Chemical Engineering Journal, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

hsa_circ_0099682 exacerbates the development of diabetic retinopathy by promoting pathological neoangiogenesis via the miR-125b-5p/HNRNPU axis - Ge Yang; Mei Xu; HongWei Zhang; Bo Zhang; YuLian Xie; YueHua Chen; Qin Hu; ZiYu Luo; Jie Lin; ZhengWen Qin (Journal of Molecular Histology, 2025)

Differences in predictions of marine species distribution models based on expert maps and opportunistic occurrences - Zhixin Zhang; Jamie M. Kass; Ákos Bede‐Fazekas; Stefano Mammola; Junmei Qu; Jorge García Molinos; Jiqi Gu; Hongwei Huang; Meng Qu; Ying Yue; Geng Qin; Qiang Lin (Conservation Biology, 2025)
Species distribution models (SDMs) are important tools for assessing biodiversity change. These models require high‐quality occurrence data, which are not always available. Therefore, it is increasingly important to determine how data choice affects predictions of species’ ranges. Opportunistic occurrence records and expert maps are both widely used sources of species data for SDMs. However, it is unclear how SDMs based on these data differ in performance, particularly for the marine realm. We built SDMs for 233 marine fish species from 2 families with these 2 occurrence data types and compared their performances and potential distribution predictions. Opportunistic occurrences were sourced from field surveys in the South China Sea and online repositories and expert maps from the International Union for Conservation of Nature Red List database. We used generalized linear models to explore drivers of differences in prediction between the 2 model types. When projecting to distinct regions with no occurrence data, models calibrated using opportunistic occurrences performed better than those using expert maps, indicating better transferability to new environments. Differences in marine predictor values between the 2 data types accounted for the dissimilarity in model predictions, likely because expert maps included large areas with unsuitable environmental conditions. Dissimilarity levels among fish families differed, suggesting a taxonomic bias in biodiversity data between data sources. Our findings highlight the sensitivity of species distribution predictions to the choice of distributional data. Although expert maps have an important role in biodiversity modeling, we suggest researchers assess the accuracy of these maps and reduce commission errors based on knowledge of target species.

Distinct neurotoxic mechanisms of thallium and lead: Calcium-mediated apoptosis and iron-induced ferroptosis in zebrafish at environmental concentrations - Jian Liu; Ai Guan; Zihui Huo; Xin Li; Yiwen Zhu; Hongwei Liang; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2025)

Interfacial models for FRP profile-concrete bolt connection considering shear-bending effects - Hongwei Lin; Erkang Gong; Peng Feng; Libo Yan; Zhongxing Wang (Engineering Structures, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Reducing Inflammation Levels and Ensuring Adequate Iodine Intake May Mitigate Thyroid Hormone Alterations in Youth Exposed to Multiple Endocrine-Disrupting Chemicals - Jia He; Fenfang Deng; Hongwei Zhou; Juan Yuan; Lin Zhang; Lei Tan (Exposure and Health, 2025)

Dynamic Modeling and Experimental Validation of Shock Isolation Performance for Shipborne Stewart-Platform-Based Bumper - Yongqiang Tu; Haoran Zhang; Yintao Li; Wei Wang; Gang Lu; Hongwei Lin; Xinkai Chen; Yan Huang; Jianyu Fan (Journal of Marine Science and Engineering, 2025)
The Stewart-platform-based bumper plays a critical role in shipborne strap-down inertial navigation systems (SINSs), effectively mitigating shock-induced disturbances to ensure measurement accuracy. Dynamic modeling for the bumper under a huge impact is a key issue in predicting the shock isolation performance of the bumper. In this paper, the dynamic modeling of shock isolation performance for Stewart-platform-based bumpers under huge impacts is proposed and validated experimentally. Firstly, a model of a Stewart-platform-based bumper is established considering the geometric configuration and dynamic parameters of the bumper by calculating the Jacobian matrix, stiffness matrix, damping matrix and mass matrix. Secondly, an analytic simulation of the impact is presented based on the measured impact acceleration, and the impact force on the load is derived according to the non-displacement assumption in the impact stage. Then, the Lagrangian formulation was systematically applied to establish governing equations characterizing the six-degree-of-freedom (DOF) dynamics of the bumper, incorporating both inertial coupling effects and nonlinear shock energy dissipation mechanisms. Afterwards, dynamic equations were solved via the Runge–Kutta method to obtain the theoretical results. Finally, the proposed dynamic modeling and shock isolation performance analysis method was validated via impact experiments for the bumper.

Corrigendum to “Redistribution of vocal snapping shrimps under climate change” [Sci. Total. Environ. 954 (2024) 176191] - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2025)

Power capture and management system of a small-scale marine current turbine for offshore instrument power supply - Yajing Gu; Tian Zou; Hongwei Liu; He Ren; Yonggang Lin (Ocean Engineering, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Deflection influence line - based bridge damage detection using high-resolution modal flexibility matrix with limited sensors - Yuming Lin; Zimo Zhu; Hongwei Ma; Zhenhua Nie (Engineering Structures, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Functional Outcome Prediction of Acute Ischemic Stroke Based on the Oral and Gut Microbiota - Jingru Liang; Yueran Ren; Yifeng Zheng; Xiaofei Lin; Wei Song; Jiajia Zhu; Xiaomei Zhang; Hongwei Zhou; Qiheng Wu; Yan He; Jia Yin (Molecular Neurobiology, 2025)

Seasonal difference in the behavior of polycyclic aromatic hydrocarbons in a large river-dominated estuary: Significance of winter sediment resuspension - Dongrui Zhang; Xiaoxia Yu; Hongwei Ren; Xueshi Sun; Lian Duan; Tian Lin; Zhigang Guo (Marine Pollution Bulletin, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Greenspace and respiratory diseases and symptoms in Chinese children: A large-scale study exploring joint associations with ozone - Pei-Pei Dong; Gongbo Chen; Yue Wen; Joachim Heinrich; Elaine Fuertes; Tianyu Zhao; Nur Sabrina Idrose; Li-Zi Lin; Zhao-Huan Gui; Xiaodi Qin; Hongwei Tu; Guang-Hui Dong (Sustainable Cities and Society, 2025)

In situ growth of iron incorporated Ni3S2 nanosheet on nickel foam in mediating electron transfer to peroxymonosulfate for pollutant abatement - Yunjin Yao; Zhongming Tao; Hongwei Hu; Lijie Zhang; Ziwei Ma; Yaoyao Wang; Shiyang Lin; Shaobin Wang (Journal of Environmental Sciences, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Surgical treatment of Meniere’s disease - Yixu Wang; Hongwei Zheng; Xin Ma; Lin Han; Tongxiang Diao; Lisheng Yu; Maoli Duan (Science Bulletin, 2025)

Antibacterial mechanisms of PLA on Aeromonas hydrophila and its application in fish disease resistance and fish preservation - Xiaohua Xia; Yanxia Lin; Yali Wang; Lu Qin; Shuang Liu; Hongwei Zhang; Xiaowen Zhang; Yi Li (Food Bioscience, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Branch-Leaf ZrO2@SiC@WS2 fibers as outstanding microwave absorber with high-temperature tolerance - Yongzhen Ma; Ying Lin; Yan Cheng; Zhixin Cai; Yanlong Ma; Binglong Zheng; Hongwei Zhou; Haibo Yang (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Promoted growth with dynamic cellular stoichiometry driven by utilization of in-situ dissolved organic matter: Insights from bloom-forming dinoflagellate Prorocentrum donghaiense - Hongwei Wang; Siyang Wu; Jian Ma; Yiting Hong; Chentao Guo; Jing Zhao; Xin Lin (Marine Environmental Research, 2025)

Quantitative proteomics provides new insights into the mechanism underlying textural property improvement in frankfurters by ultrasound treatment combined with κ-carrageenan - Shiwen Lin; Zhigang Sun; Cheng Li; Baohua Kong; Chuanai Cao; Xiufang Xia; Hongwei Zhang; Qian Liu (Food Hydrocolloids, 2025)

Mechanical properties of a novel fiber-bridging interface for connecting FRP profile and concrete - Hongwei Lin; Haidong Qu; Peng Feng; Huixin Zeng; Guanzhi Cheng (Engineering Structures, 2025)

Efficient approach for ground dynamic impedance function of the large-scale nuclear power plant footing under a layered site considering the embedded effect - Jianbo Li; Hongwei Hou; Zhiyuan Li; Gao Lin (Computers and Geotechnics, 2025)

D-Histidine modulated chiral metal-organic frameworks for discriminating 3,4-Dihydroxyphenylalanine enantiomers based on a chemiluminescence quenching mode - Xinyue Gao; Ruining Bai; Jin Yang; Shuai Luo; Hongwei Yuan; Lin Wang; Zhifeng Fu (Analytica Chimica Acta, 2025)

Host-intestinal microbiota interactions in Edwardsiella piscicida-induced lethal enteritis in big-belly seahorses: Novel insights into the role of Carbohydrate-Active enzymes and host transcriptional responses - Longwu Jia; Lele Zhang; Hongwei Yang; Lin Li; Shiyi Zheng; Yicong Ma; Yuanyuan Xue; Jingyi Zhang; Mingzhu Li; Xiaolei Su; Kai Wang (Fish & Shellfish Immunology, 2025)

Local contributions and climate change effects on organochlorine pesticide levels in soil and sediments in Svalbard - Yan Lin; Geir Wing Gabrielsen; Zhibo Lu; Qinghui Huang; Peng Huang; Hongwei ke; Minggang Cai (Environmental Pollution, 2025)

Redistribution of vocal snapping shrimps under climate change - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2024)

High-resolution 3D hydrodynamic modeling and comprehensive assessment of tidal current energy resources - Tian Zou; Yajing Gu; Hongwei Liu; Yonggang Lin; Liyuan Zhang; Yuquan Zhang (Ocean Engineering, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Unraveling size-dependent catalytic activity of monolithic alginate hydrogels for PMS activation and ciprofloxacin removal - Jie Lin; Yunxiong Zeng; Xingyu Zhan; Jingcai Xu; Xinqing Wang; Bo Hong; Xiaoling Peng; Jing Li; Hongwei Chen; Yingchun Xia (Journal of Environmental Chemical Engineering, 2024)

Improving the accuracy and interpretability of multi-scenario building energy consumption prediction considering characteristics of training dataset - Haizhou Fang; Hongwei Tan; Xiaolei Yuan; Xiaojie Lin; Dafang Zhao; Risto Kosonen (Energy and Buildings, 2024)

Novel Pathogenic Mutation of P209L in TRPC6 Gene Causes Adult Focal Segmental Glomerulosclerosis - Tianxi Yu; Yongqiang Ji; Xin Cui; Ning Liang; Shuang Wu; Chongjun Xiang; Yue Li; Huiying Tao; Yaqi Xie; Hongwei Zuo; Wenting Wang; Nauman Khan; et al. (Biochemical Genetics, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Global mapping of human-transformed dike-pond systems - Yang Xu; Lian Feng; Hongwei Fang; Xiao-Peng Song; Fabian Gieseke; Ankit Kariryaa; Stefan Oehmcke; Luke Gibson; Xiating Jiang; Ruimin Lin; R. Iestyn Woolway; Chunmiao Zheng; et al. (Remote Sensing of Environment, 2024)

Constructing SDBS-intercalated MoS2 nanosheets confined and near-vertically grown on network biochar adsorbent: Insights into highly efficient co-adsorption of ciprofloxacin and lead ions - Yang Wang; Xinyao Liu; Xinru Lin; Hongwei Yuan; Mingxia Liu; Lei Zhang (Chemical Engineering Journal, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Can Smart city policies enhance corporate environmental performance? Evidence from China - Hongwei Shao; Xuecong Tang; Xiyan Xiao; Yanna Ma; Ziqiang Lin (Environment, Development and Sustainability, 2024)

Achieving efficient electromagnetic absorption in multifunctional carbon nanotube aerogels by manipulating radialized network structure - Zhixin Cai; Haibo Yang; Hongwei Zhou; Ying Lin; Yan Cheng; Qibin Yuan (Chemical Engineering Journal, 2024)

Characteristics of acidic hydrothermal treatment for disintegration of spiramycin fermentation residue and degradation of residual antibiotics - Gang Wang; Quancheng Shu; Jinzhi Sun; Yucan Liu; Xiaoyong Yang; Hao Lin; Jing Ding; Yanxiang Zhang; Lijuan Lan; Hongwei Sun (Bioresource Technology, 2024)

Influence of axial stress on rockburst in deep tunnels: insight from model experiment - Yaofeng Yan; Yuanyou Xia; Jian Huang; Manqing Lin; Xiqi Liu; Minjia Yan; Hongwei Zhang (Journal of Mountain Science, 2024)

Potential mechanisms and effects of ultrasound treatment combined with pre- and post-addition of κ-carrageenan on the gelling properties and rheological behavior of myofibrillar proteins under low-salt condition - Shiwen Lin; Xin Li; Jingming Zhang; Baohua Kong; Chuanai Cao; Fangda Sun; Hongwei Zhang; Qian Liu; Chunyan Liu (Meat Science, 2024)

A novel hybrid framework based on modified continued-fraction for pile-soil dynamic interaction of large-scale nuclear power structures - Jianbo Li; Hongwei Hou; Zhiyuan Li; Gao Lin (Computers and Geotechnics, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

The Footprints of Mitochondrial Fission and Apoptosis in Fluoride-Induced Renal Dysfunction - Qiyong Zuo; Lin Lin; Yuling Zhang; Mohammad Mehdi Ommati; Hongwei Wang; Jing Zhao (Biological Trace Element Research, 2024)

A novel integrated urban flood risk assessment approach based on one-two dimensional coupled hydrodynamic model and improved projection pursuit method - Lin Yan; Hongwei Rong; Weichao Yang; Jianxin Lin; Chuanxing Zheng (Journal of Environmental Management, 2024)

Antibacterial and anti-inflammatory synergistic effects of double-layer hydrogel promoting bacterial wound healing - Chunyang Li; Jin-Tao Wang; Kuili Liu; Hongwei Ding; Qing-Feng Li; Gaofeng Liang; Lin Jin; Deyan He (Chemical Engineering Journal, 2024)

Soat2 inhibitor avasimibe alleviates acute pancreatitis by suppressing acinar cell ferroptosis - Weiwei Luo; Lin Chen; Hui Sun; Siqin Zhang; Xiaowu Dong; Jiajia Pan; Weiming Xiao; Guotao Lu; Yaodong Wang; Hongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Indirect load measurement method and experimental verification of floating offshore wind turbine - Xiangheng Feng; Yonggang Lin; Yajing Gu; Xingchen Zhao; Hongwei Liu; Yong Sun (Ocean Engineering, 2024)

N6-methyladenosine modified lncRNAs signature for stratification of biochemical recurrence in prostate cancer - Yingke Liang; Wenjun Yin; Zhouda Cai; Hongwei Luo; Qinwei Liu; Chuanfan Zhong; Jiahong Chen; Zhuoyuan Lin; Yaqiang Huang; Zhenguo Liang; Junhong Deng; Weide Zhong; et al. (Human Genetics, 2024)

A three-step rockburst prediction model based on data preprocessing combined with clustering and classification algorithms - Hongwei Zhang; Yuanyou Xia; Manqing Lin; Jian Huang; Yaofeng Yan (Bulletin of Engineering Geology and the Environment, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Chronology by luminescence and radiocarbon on core sediments from the northeastern pearl river plain and implications for delta process - Penghui Lin; Xian Hu; Weiqi Zhan; Yucong Chen; Ken Ling; Bingfa Zhi; Hongwei Li; Zhongping Lai (Quaternary Geochronology, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Numerical Study on the Flow Field Characteristics and Dust Removal Efficiency of Tubular Electrofiltration Equipment - Zhifan Zhang; Lin Zhang; Gang Yang; Xi Zhang; Chengman Zhou; Jiayong Wu; Hongwei Qian; Hanqing Shao; Jiakai Zhang (Aerosol Science and Engineering, 2024)

Status and Challenges of Marine Current Turbines: A Global Review - Yajing Gu; Tian Zou; Hongwei Liu; Yonggang Lin; He Ren; Qingjun Li (Journal of Marine Science and Engineering, 2024)
Over the past few decades, marine current energy utilization has transitioned from conceptual demonstrations to industrial-scale prototypes. This progression now approaches a crucial phase emphasizing the need for industrialization and commercialization. This paper provides an in-depth examination of the developmental status of large-scale marine current turbines and arrays, underscoring the promising prospects for marine current energy systems. Despite the significant advancements, the deployment of these systems has revealed several challenges, including blade design optimization, transmission system selection, and the establishment of appropriate test sites. Addressing these issues is essential for technological maturity and economic feasibility, which will foster the next wave of innovation in marine energy systems. Furthermore, the paper offers various perspectives for future applications.

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

Dual modification engineering enabled efficient perovskite solar cells with high open-voltage of 1.233 V - Zhongqi Liu; Long Shao; Fancong Zeng; Shuhang Bian; Bin Liu; Yuqi Wang; Yanjie Wu; Yongzhi Shao; Huan Zhang; Yuhong Zhang; Zhicong Shi; Xue Bai; et al. (Chemical Engineering Journal, 2024)

Isolation, identification and whole-genome analysis of an Achromobacter strain with a novel sulfamethazine resistance gene and sulfamethazine degradation gene cluster - Luping Zeng; Hongwei Du; Xianke Lin; Ruomei Liao; Ying Man; Huaiyang Fang; Yang Yang; Ran Tao (Bioresource Technology, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Correction to: Geotechnical characterization of the diatomaceous silty soil in Walvis Bay, Namibia: mechanical properties and interpretations of CPTu records - Jianyu Li; Hongjie Lin; Yue Zhang; Hongwei Yang; Jiankun Liu (Bulletin of Engineering Geology and the Environment, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

Long-term phytoextraction potential and mechanism of Celosia argentea on soils with different levels of Cd and Mn co-contamination - Guo Yu; Habib Ullah; Hua Lin; Geoffrey I. Sunahara; Xuehong Zhang; Baoliang Chen; Hongwei Yu; Asfandyar Shahab; Liheng Liu; Jie Liu (Journal of Environmental Chemical Engineering, 2024)

An in-situ combo Mo-based ionic liquid and SAPO-11 catalyst for efficient biolipids hydrodeoxygenation and isomerization - Yongxin Ding; Jun Lin; Panjie Yu; Hongwei Zhang; Yongde Ma; Zhenping Cai; Yanning Cao; Kuan Huang; Lilong Jiang (Fuel, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Geotechnical characterization of the diatomaceous silty soil in Walvis Bay, Namibia: mechanical properties and interpretations of CPTu records - Jianyu Li; Hongjie Lin; Yue Zhang; Hongwei Yang; Jiankun Liu (Bulletin of Engineering Geology and the Environment, 2024)

The paradigm for exceptional iodine capture by nonporous amorphous electron-deficient cyclophanes - Baoqi Wu; Zhi-Wei Li; Feng Lin; Rongzhi Tang; Wanqing Zhang; Hongwei Liu; Gangfeng Ouyang; Yu Tan (Journal of Hazardous Materials, 2024)

Characteristics and fractionations of sediment oxygen demand in a complex tidal river network area - Zhiwei Huang; Xiaochen Liu; Jing Wen; Huaiyang Fang; Shu Lin; Weijie Li; Jie Wang; Fantang Zeng; Hongwei Du; Lei Shi (Journal of Environmental Management, 2024)

Deep convolutional neural networks for aged microplastics identification by Fourier transform infrared spectra classification - Ganning Zeng; Yuan Ma; Mingming Du; Tiansheng Chen; Liangyu Lin; Mengzheng Dai; Hongwei Luo; Lingling Hu; Qian Zhou; Xiangliang Pan (Science of The Total Environment, 2024)

Foraging behavior and sea ice-dependent factors affecting the bioaccumulation of mercury in Antarctic coastal waters - Lin Yang; Ben Yu; Hongwei Liu; Xiaomeng Ji; Cailing Xiao; Mengxi Cao; Jianjie Fu; Qinghua Zhang; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Science of The Total Environment, 2024)

Investigation of the mechanism of silica-induced pulmonary fibrosis: The role of lung microbiota dysbiosis and the LPS/TLR4 signaling pathway - Qiyue Jia; Hongwei Wang; Yan Wang; Wenming Xue; Qiyue Jiang; Jiaxin Wang; Fuao Ning; Zhonghui Zhu; Lin Tian (Science of The Total Environment, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Meshless numerical manifold method with novel subspace tracking and CSS locating techniques for slope stability analysis - Xitailang Cao; Shan Lin; Zenglong Liang; Hongwei Guo; Hong Zheng (Computers and Geotechnics, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Effect of the IGF-1/PI3K/AKT Pathway on the Proliferation of Mouse bone Marrow Mesenchymal stem Cells under Negative Pressure Modulation - Xiya Wu; Zhiyi Lin; Jie Cui; Xiongfeng Yang; Hongwei Zhang; Renyi Jing (Stem Cell Reviews and Reports, 2024)

Warming effects on C:N:P stoichiometry and nutrient limitation in terrestrial ecosystems - Hongwei Xu; Minggang Wang; Chengming You; Bo Tan; Lin Xu; Han Li; Li Zhang; Lixia Wang; Sining Liu; Guirong Hou; Yang Liu; Zhenfeng Xu; et al. (Soil and Tillage Research, 2024)

Early-stage fertilization detection in pigeon eggs during incubation using improved lightweight model - Zhanhong Hou; Ken Cai; Gengsheng Xiao; Qiusen Fang; Yanzhu Feng; Huazhou Chen; Hongwei Yue; Ziying Wang; Qinyong Lin (Computers and Electronics in Agriculture, 2023)

Can water dating trace the transport history of HCHs in the ocean? - Weimin Wang; Haowen Zheng; Peng Huang; Jiandong Ye; Mengyang Liu; Yan Lin; Yifan Li; Mian Chen; Hongwei Ke; Minggang Cai (Science of The Total Environment, 2023)

Degradation of ribavirin by potassium ferrate(Ⅵ): Kinetics, degradation pathway and toxicity assessment - Zheng Li; Qiping Zheng; Kaicong Cai; Lin Yang; Jinkun Yang; Hongwei Sun; Changqing Liu; Weifang Zhang; Yuyi Zheng; Chunshan Wu (Process Safety and Environmental Protection, 2023)

Micromechanics-based model of rock considering compaction deformation: Analysis of microcrack influence from discrete and continuous perspectives - Huiguan Chen; Cheng Zhao; Rui Zhang; Lin Huang; Haoyu Pan; Yuan Qian; Hongwei Yang (Computers and Geotechnics, 2023)

Transient thermal–hydraulic analysis of the thermionic space reactor TOPAZ-II - Zongyun Wu; Lin Qi; Lin Sun; Mingyu Wu; Hongwei Yang; Tiancai Liu (Annals of Nuclear Energy, 2023)

Decoding the marine biogeochemical cycling of mercury by stable mercury isotopes - Lin Yang; Ben Yu; Deming Han; Kun Zhang; Hongwei Liu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Diffusion kurtosis imaging tractography reveals disrupted white matter structural networks in children with obstructive sleep apnea syndrome - Yanhua Li; Hongwei Wen; Wenfeng Li; Yun Peng; Hongbin Li; Jun Tai; Tingting Ji; Lin Mei; Yue Liu (Brain Imaging and Behavior, 2023)

Holocene Evolution of the Pearl River Delta: Mapping Integral Isobaths and Delta Progradation - Yongjie Tang; Zhuo Zheng; Kangyou Huang; Cong Chen; Zhen Chen; Hongyu Lu; Weisheng Wu; Xiaoming Lin; Xianhe Zhang; Hongwei Li (Journal of Marine Science and Engineering, 2023)
The Pearl River Delta (PRD, China) has undergone complex geological development within a multi-island faulted basin, shaped by the interplay of regional tectonic movements, Quaternary sea-level fluctuations, and fluvial-marine interactions. Despite a great number of studies on the Holocene sedimentary sequences and spatial differences of lithofacies and environments, scant attention has been paid to the overarching human influence on deltaic evolution and coastline modifications since the Neolithic epoch. To further elucidate the spatial variation in Holocene sedimentation and its underlying basement topography shaped during the Last Glacial Maximum (LGM), we compiled a comprehensive dataset incorporating borehole data from over 2800 cores (the maximum depth can reach 92.5 m) within the PRD. Subsequently, high-resolution isobath maps of Quaternary deltaic deposits were generated, offering unprecedented insights into sediment distribution. This dataset facilitated a nuanced reconstruction of pre-Holocene topography, revealing a zone characterized by elongated, deep-incised valleys governed by NW-SE fault orientations. Further, we delineated coastline shifts since the period of maximum Holocene transgression (~7000 years BP), contributing to an enhanced understanding of the formation and evolutionary patterns of the delta and river network oscillations. Our findings illuminate an increasing anthropogenic impact on the rate of fluvial sedimentation and land growth, particularly accentuated over the last two millennia, favoring deltaic accretion.

Preliminary stability design method and hybrid experimental validation of a floating platform for 10 MW wind turbine - Xiangheng Feng; Yonggang Lin; Yajing Gu; Danyang Li; Bowen Chen; Hongwei Liu; Yong Sun (Ocean Engineering, 2023)

Heavy metals and Pb isotopes in sediment cores from the Bering and Chukchi seas: Implications for environmental changes and human activities over the past century - Yan Lin; Zhai Wu; Hongwei Ke; Huorong Chen; Ye Xu; Jin Lin; Yanguang Liu; Fangjian Xu; Dongren Huang; Yi Wang; Tianyao Li; Minggang Cai (Marine Environmental Research, 2023)

Bond behavior of FRP-concrete wet-bonding interface under lateral confinement - Hongwei Lin; Huixin Zeng; Peng Feng; Cheng Jiang; Yuqing Zhang (Engineering Structures, 2023)

A fatigue constitutive model for rock masses based on cross-applications of rheological theory - Xing Zhang; Hang Lin; Hongwei Liu; Su Li; Jiangteng Li; Jinci Chen (European Journal of Environmental and Civil Engineering, 2023)

Analytical method for predicting tunnel heave due to overlying excavation considering spatial effect - Kang Cheng; Riqing Xu; Hongwei Ying; Cungang Lin; Xiaolu Gan; Xiaonan Gong; Jianfeng Zhu; Sijie Liu (Tunnelling and Underground Space Technology, 2023)

Elevated methylmercury in Antarctic surface seawater: The role of phytoplankton mass and sea ice - Fange Yue; Yanbin Li; Yanxu Zhang; Longquan Wang; Dan Li; Peipei Wu; Hongwei Liu; Lijin Lin; Dong Li; Ji Hu; Zhouqing Xie (Science of The Total Environment, 2023)

Effects of livestock grazing on the relationships between soil microbial community and soil carbon in grassland ecosystems - Hongwei Xu; Chengming You; Bo Tan; Lin Xu; Yang Liu; Minggang Wang; Zhenfeng Xu; Jordi Sardans; Josep Peñuelas (Science of The Total Environment, 2023)

A Novel Near-Infrared Ratiometric Fluorescence Probe for Hg2+ Based on Quinoline-Fused Rhodamine Dye - Weiping Lai; Yanfei Lin; Tianqing Ye; Yating Yu; Hongwei Zhou; Lei Li; Guoliang Mao; Jianbo Wang (Journal of Fluorescence, 2023)

Natural iron minerals in an electrocatalytic oxidation system and in situ pollutant removal in groundwater: Applications, mechanisms, and challenges - Ganning Zeng; Ji Wang; Mengzheng Dai; Yutong Meng; Hongwei Luo; Qian Zhou; Liangyu Lin; Kunpeng Zang; Zhu Meng; Xiangliang Pan (Science of The Total Environment, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Hydroxyl radicals in natural waters: Light/dark mechanisms, changes and scavenging effects - Ganning Zeng; Ming Shi; Mengzheng Dai; Qian Zhou; Hongwei Luo; Liangyu Lin; Kunpeng Zang; Zhu Meng; Xiangliang Pan (Science of The Total Environment, 2023)

A natural variation in the promoter of GRA117 affects carbon assimilation in rice - Qi Wang; Shenglong Yang; Mingqian Fan; Pulin Feng; Lin Zhu; Hongwei Chen; Jiayu Wang (Planta, 2023)

The impact of oil shocks from different sources on China's clean energy metal stocks: An analysis of spillover effects based on a time-varying perspective - Yaoqi Guo; Fengyuan Shi; Boqiang Lin; Hongwei Zhang (Resources Policy, 2023)

Collective pitch for horizontal axis marine current turbine - Hongwei Liu; Haitao Li; Yajing Gu; Yonggang Lin; Bingling Xie (Ocean Engineering, 2023)

Policy impact on microplastic reduction in China: Observation and prediction using statistical model in an intensive mariculture bay - Kazi Belayet Hossain; Yan Lin; Kai Chen; Mingyu Zhang; Mengyang Liu; Wenlu Zhao; Hongwei Ke; Fengjiao Liu; Chunhui Wang; Minggang Cai (Science of The Total Environment, 2023)

A topical platelet-independent multilevel clotting initiator for intraoperative hemostasis - Fenglin Miao; Huirong Lin; Tianhong Yao; Ruyi Zhang; Xinfei Sun; Hongwei Cheng; Lingwei Gu; Xiaogang Xia; Ting Wu; Wengang Li; Gang Liu (Chemical Engineering Journal, 2023)

The onset process of the 2018/2019 Indonesian–Australian summer monsoon: The importance of the air–sea interaction - Yongliang Duan; Hongwei Liu; Ming Feng; Xiangzhou Song; Kuiping Li; Lin Liu; Baochao Liu; Guang Yang; Weidong Yu (Frontiers in Marine Science, 2023)
The Madden–Julian oscillation (MJO) and its associated air–sea interactions during the onset process of the 2018/2019 Indonesian–Australian summer monsoon (IASM) are investigated based on the in situ data from a moored buoy off the coast of northwest Australia, along with ERA5 reanalysis and satellite data. The results verify that the IASM onset in mid-December 2018 was triggered by the first-branch eastward-propagating MJO (FEMJO) originating from the tropical Indian Ocean. However, the strong negative SST anomaly (SSTA) was evident off northwest Australia, which weakens FEMJO over northern Australia and shifts the convective center further northward. The mixed layer heat budget analysis based on the buoy observations reveals that the increased latent heat loss that occurred before the arrival of the FEMJO convection was primarily attributed to the large air–sea temperature difference and strong winds, resulting in the pronounced SSTA.

The chloroplast GATA-motif of Mahonia bealei participates in alkaloid-mediated photosystem inhibition during dark to light transition - Jiaqi Chen; Tianfu Jiang; Jiajun Jiang; Linfang Deng; Yiting Liu; Zhuoheng Zhong; Hongwei Fu; Bingxian Yang; Lin Zhang (Journal of Plant Physiology, 2023)

SATB1/SLC7A11/HO-1 Axis Ameliorates Ferroptosis in Neuron Cells After Ischemic Stroke by Danhong Injection - Sikai Zhan; Jiayin Liang; Huiting Lin; Jiale Cai; Xinxin Yang; Hongwei Wu; Junying Wei; Shumei Wang; Minghua Xian (Molecular Neurobiology, 2023)

Experimental investigation on spontaneous combustion oxidation characteristics and stages of coal with different metamorphic degrees - Baisheng Nie; Hongwei Yan; Peijun Liu; Zongyu Chen; Chao Peng; Xiaotong Wang; Feifei Yin; Jie Gong; Yueying Wei; Shuangshuang Lin; Qiang Gao; Mingwei Cao (Environmental Science and Pollution Research, 2023)

A microfluidic immunosensor based on magnetic separation for rapid detection of okadaic acid in marine shellfish - Yuxiang Ji; Gaozhe Cai; Cheng Liang; Zehang Gao; Weimin Lin; Zizhen Ming; Shilun Feng; Hongwei Zhao (Analytica Chimica Acta, 2023)

WSL214 negatively regulates ROS accumulation and pathogen defense response in rice - Qi Wang; Hongwei Chen; Lin Zhu; Pulin Feng; Mingqian Fan; Jiayu Wang (Plant Cell Reports, 2022)

Dominant complementation of biological pathways in maize hybrid lines is associated with heterosis - Tao Zhou; Rabail Afzal; Muhammad Haroon; Yuting Ma; Hongwei Zhang; Lin Li (Planta, 2022)

Proteomic analysis of the spineless cuttlefish Sepiella japonica: Exploratory analyses on the phenomenon of death after spawning - Hongfei Li; Shuangrui Lin; Pengzhi Qi; Jingtian Wang; Meihua Fan; Hongwei Huang; Zhenyu Dong; Kaida Xu; Baoying Guo (Frontiers in Marine Science, 2022)
To better understand the physiological events involving death after spawning in S. japonica (Japanese spineless cuttlefish), we have presently generated a proteomic data set to properly examine this phenomenon. As such, a proteomic-based approach was employed to identify differentially expressed proteins (DEPs) in the optic glands of S. japonica , at three distinct growth stages: pre-spawning after sexual maturity (group A); spawning (group B) and postspawning before death (group C). About 955, 1000, and 1024 DEPs were identified for each comparative group analysis (i.e., group B vs A, group B vs C, and group C vs A). We further discovered that the function of these newly identified DEPs was mostly related to molecular events such as gene translation and signal transduction. According to the enriched GO terms obtained by Gene Ontology analysis, the function of most DEPs was correlated with structural molecule activity, ribosome function and gene expression. The majority of DEPs were known to be involved in signal transduction and energy metabolism, interestingly, some aging-related DEPs were also identified. Putting together, our study provides new insights, at the protein level, in the phenomenon of death after spawning in S. japonica , by referring to anti-aging effects conserved in other cephalopoda species.

A Discontinuous Individual Growth Model of Swimming Crab Portunus trituberculatus and Its Application in the Nutrient Dynamic Simulation in an Intensive Mariculture Pond - Shipeng Dong; Xian Xu; Fan Lin; Liye Yu; Hongwei Shan; Fang Wang (Frontiers in Marine Science, 2022)
Environmental problems such as organic pollution and eutrophication caused by highly intensive mariculture activities constrain the sustainable and healthy development of industry. Therefore, it is necessary to quantify the nutrient dynamics of aquaculture animals in order to reduce the risk of environmental pollution. In this study, a discontinuous individual growth model of Portunus trituberculatus in an intensive mariculture pond of P. trituberculatus – Penaeus japonicus – Sinonovacula constricta was constructed based on a dynamic energy budget theory combined with the index of condition factor. This model better predicted the growth and molting behavior of P. trituberculatus , and an acceptable fit was obtained through model parameterization using the Add-my-Pet (AmP) method (mean relative error = 0.058, symmetric mean squared error = 0.007). Ten molts were simulated over 180 days and generally coincided with the recorded molt time points. Based on this model and P. trituberculatus populations, the dynamic processes of carbon, nitrogen, and phosphorus in ingestion, respiration, excretion, feces, residual feed, dead crabs, seeding, molt, and harvest were simulated. The carbon, nitrogen, and phosphorus ingested during the 180-day culture period were 4,938.57 kg ha -1 , 1,255.88 kg ha -1 , and 244.16 kg ha -1 , respectively. Carbon, nitrogen, and phosphorus removal by harvest accounted for 1.06%, 1.03% and 0.62% of the total ingestion, respectively, while carbon, nitrogen, and phosphorus removal by dead crabs accounted for 6.84%, 6.63%, and 4.04%, respectively, and carbon, nitrogen, and phosphorus released from residual feed into the water accounted for 41.43% of the total feed. The accurate simulation of molting behavior and nutrient dynamics in this study provides a theoretical basis for molting risk prevention and environmental stress assessment of P. trituberculatus and provides basic modules and data support for the construction of the integrated mariculture ecosystem model.

Hydrodynamic Analysis of Tidal Current Turbine under Water-Sediment Conditions - Yanjing Gao; Hongwei Liu; Yonggang Lin; Yajing Gu; Yiming Ni (Journal of Marine Science and Engineering, 2022)
The rivers connecting oceans generally carry sediment due to water and soil losses in China. Additionally, the maximum sediment concentration is 300 g/L, which is much higher than that of other countries. It is unknown whether seawater with sand particles will affect the power of tidal current turbine blades. It is therefore necessary to study the capture power of tidal current turbines in the water-sediment environment. In this study, the blade was divided into a number of transversal airfoil elements based on the blade element theory. The CFD-DPM model was employed to study the lift and drag coefficients of airfoil under multiphase flow, and the fluid–particle interaction was considered. The accuracy of this presented model was assessed using the experimental data of a 120 kW tidal current turbine in a water-sediment environment. Good agreement between the predictions and experimental data was observed. The effect of particle properties on the lift coefficient and the drag coefficient of airfoil were investigated in detail. Furthermore, the 120 kW tidal current turbine power was calculated based on the Blade Element Momentum theory under different particle concentrations. The results show that small diameter particles can improve the tidal current turbine power and the large diameter particle can reduce the power.

Evaluation on explosion characteristics and parameters of pulverized coal for low-quality coal: experimental study and analysis - Hongwei Yan; Baisheng Nie; Chao Peng; Peijun Liu; Xiaotong Wang; Feifei Yin; Jie Gong; Yueying Wei; Shuangshuang Lin; Qiang Gao; Mingwei Cao (Environmental Science and Pollution Research, 2022)

Dopaminergic Projection from Ventral Tegmental Area to Substantia Nigra Pars Reticulata Mediates Chronic Social Defeat Stress–Induced Hypolocomotion - Feng He; Pei Zhang; Qian Zhang; Guangjian Qi; Hongwei Cai; Tongxia Li; Ming Li; Jiazhen Lu; Jiaen Lin; Jie Ming; Bo Tian (Molecular Neurobiology, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Visual detection of tropomyosin, a major shrimp allergenic protein using gold nanoparticles (AuNPs)-assisted colorimetric aptasensor - Tushar Ramesh Pavase; Hong Lin; Maqsood Ahmed Soomro; Hongwei Zheng; Xiaxia Li; Kexin Wang; Zhenxing Li (Marine Life Science & Technology, 2021)

Mid-Level Riverine Outflow Matters: A Case of Microplastic Transport in the Jiulong River, China - Yifan Li; Siguang Liu; Mengyang Liu; Wei Huang; Kai Chen; Yongcheng Ding; Fangzhu Wu; Hongwei Ke; Linghao Lou; Yan Lin; Mingyu Zhang; Fengjiao Liu; et al. (Frontiers in Marine Science, 2021)
Riverine outflow is one of the major pathways for microplastic transportation to coastal environments. Research on the output of microplastics in small- or medium-sized rivers will help accurately understand the status of their marine loads. In this study, we used both trawling and pumping methods to collect microplastics of different sizes in the Jiulong River Estuary and Xiamen Bay. We found that the abundance of small microplastics (44 μm–5.0 mm) was at least 20 times higher than the large particles (0.33–5.0 mm). The abundance of the large particles ranges from 4.96 to 16.3 particles/m 3 , and that of the small particles ranged from 82.8 to 918 particles/m 3 . Granule was the dominant shape (>60%), and polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) were the most common components. The riverine flux of small microplastics (44 μm–5 mm, 472 ± 230 t/y) was at a medium level and was eight times greater than that of large particles (0.33–5.0 mm, 61.2 ± 2.6 t/y). The behavior of the large microplastics was relatively conservative, whose abundance had a significant correlation with salinity ( R 2 = 0.927) and was mainly influenced by physical factors. In contrast, results of statistical analysis revealed that more complicated factors influenced the small microplastics.

Influence of Combined Motion of Pitch and Surge with Phase Difference on Aerodynamic Performance of Floating Offshore Wind Turbine - Xiangheng Feng; Yonggang Lin; Guohao Zhang; Danyang Li; Hongwei Liu; Bin Wang (Journal of Marine Science and Engineering, 2021)
Platform motions induced by waves pose a challenge to accurately predict the aerodynamic performance of floating offshore wind turbines (FOWTs). In view of this, the power performance and wake structure of FOWTs under platform pitch, surge, and their combined motions were investigated in this paper, using the computational fluid dynamics software, STAR-CCM+, with overset meshing and rigid body motion techniques. First, the simulation cases in single and same-phase combined motions with different amplitudes and frequencies were performed. Afterward, the approach of calculating the phase difference between pitch and surge motions was proposed to investigate the influence of the combined motion with phase difference on the aerodynamic performance. Results show that the increment of amplitude and frequency augments the mean power output and aggravates the power fluctuation in single and same-phase combined motions. The intensity of power variation under combined motion with a phase difference is weakened at 0.1 Hz compared to the single motion, while enhanced at 0.2 Hz, showing a different influence law on the aerodynamic performance. In addition, this paper established the power fluctuation table based on real sea states of Shidao in China, providing a certain reference for the controller design in this sea area.

Maternal Separation-Induced Histone Acetylation Correlates with BDNF-Programmed Synaptic Changes in an Animal Model of PTSD with Sex Differences - Haoran Sun; Xianqiang Zhang; Yujia Kong; Luping Gou; Bo Lian; Yanyu Wang; Li Jiang; Qi Li; Hongwei Sun; Lin Sun (Molecular Neurobiology, 2021)

3-Dimensional Modeling and Attitude Control of Multi-Joint Autonomous Underwater Vehicles - Lin Yu; Qinghao Meng; Hongwei Zhang (Journal of Marine Science and Engineering, 2021)
To achieve rapid and flexible vertical profile exploration of deep-sea hybrid structures, a multi-joint autonomous underwater vehicle (MJ-AUV) with orthogonal joints was designed. This paper focuses on the 3-dimensional (3D) modeling and attitude control of the designed vehicle. Considering the situation of gravity and buoyancy imbalance, a 3D model of the MJ-AUV was established according to Newton’s second law and torque balance principle. And then the numerical simulation was carried out to verify the credibility of the model. To solve the problems that the pitch and yaw attitude of the MJ-AUV are coupled and the disturbance is unknown, a linear quadratic regulator (LQR) decoupling control method based on a linear extended state observer (LESO) was proposed. The system was decoupled into pitch and yaw subsystems, treated the internal forces and external disturbances of each subsystem as total disturbances, and estimated the total disturbances with LESO. The control law was divided into two parts. The first part was the total disturbance compensator, while the second part was the linear state feedback controller. The simulation results show that the overshoot of the controlled system in the dynamic process is nearly 0 rad, reaching the design value very smoothly. Moreover, when the controlled system is in a stable state, the control precision is within 0.005%.

Correction to: IL-17A Induces MIP-1α Expression in Primary Astrocytes Via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin Lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2021)

Intraseasonal modulation of Wyrtki jet in the eastern Indian Ocean by equatorial waves during spring 2013 - Yongliang Duan; Hongwei Liu; Lin Liu; Weidong Yu (Acta Oceanologica Sinica, 2020)

Electroacupuncture ameliorates learning and memory deficits via hippocampal 5-HT1A receptors and the PKA signaling pathway in rats with ischemic stroke - Zhifu Wang; Bingbing Lin; Weilin Liu; Hongwei Peng; Changming Song; Jia Huang; Zuanfang Li; Lidian Chen; Jing Tao (Metabolic Brain Disease, 2020)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

Sedimentological characteristics and controlling factors on fluvial styles of the Guantao Formation, Kongdian Oilfield, China - Hai Liu; Chengyan Lin; Xianguo Zhang; Hongwei Wang; Xiaoliang Fu (Journal of Earth System Science, 2019)

Gas Pressure Prediction Model for Carbon Dioxide Injection in a Large-Scale Coal Matrix Experiment - Wen Nie; Lin Chen; Xin Wu; Hongwei Yang; Bobo Li; Yidu Hong; Yulong Chen (Rock Mechanics and Rock Engineering, 2019)

In vitro assessment of the toxicity of small silver nanoparticles and silver ions to the red blood cells - Zhenxing Chi; Hongwei Lin; Weiguo Li; Xunuo Zhang; Qiang Zhang (Environmental Science and Pollution Research, 2018)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Tension force-induced bone formation in orthodontic tooth movement via modulation of the GSK-3β/β-catenin signaling pathway - Yelin Mao; Liangliang Wang; Ye Zhu; Yu Liu; Hongwei Dai; Jianping Zhou; Dechun Geng; Lin Wang; Yong Ji (Journal of Molecular Histology, 2018)

Investigation of Intrinsic and External Factors Contributing to the Occurrence of Coal Bumps in the Mining Area of Western Beijing, China - Hongwei Wang; Yaodong Jiang; Sheng Xue; Xufeng Pang; Zhinan Lin; Daixin Deng (Rock Mechanics and Rock Engineering, 2017)

TIMAP repression by TGFβ and HDAC3-associated Smad signaling regulates macrophage M2 phenotypic phagocytosis - Jun Yang; Shasha Yin; Fangfang Bi; Lin Liu; Tian Qin; Hongwei Wang; Wangsen Cao (Journal of Molecular Medicine, 2017)

Tracking fluorescent components of dissolved organic matter from soils in large-scale irrigated area - Hongwei Pan; Huibin Yu; Yonghui Song; Lin Zhu; Ruixia Liu; Erdeng Du (Environmental Science and Pollution Research, 2017)

Comparison of Kinetics of Arsenic(V) Adsorption on Two Types of Red Soil Weathered from Granite and Sandstone - Hongwei Chen; Lin Liu; Rouyan Gong; Runchu Wei; Qiaohui Yi; Anni Qiu (Water, Air, & Soil Pollution, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Ya-fish (Schizothorax prenanti) spexin: identification, tissue distribution and mRNA expression responses to periprandial and fasting - Hongwei Wu; Fangjun Lin; Hu Chen; Ju Liu; Yundi Gao; Xin Zhang; Jin Hao; Defang Chen; Dengyue Yuan; Tao Wang; Zhiqiong Li (Fish Physiology and Biochemistry, 2016)

Endothelial progenitor cells as a possible component of stem cell niche to promote self-renewal of mesenchymal stem cells - Hongwei Zhang; Lingling Xian; Zhiyi Lin; Chaozhe Yang; Meng Zhang; Wenlei Feng; Xinyu Peng; Xueling Chen; Xiangwei Wu (Molecular and Cellular Biochemistry, 2014)

IL-17A Induces MIP-1α Expression in Primary Astrocytes via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2014)

Schizothorax prenanti corticotropin-releasing hormone (CRH): molecular cloning, tissue expression, and the function of feeding regulation - Tao Wang; Chaowei Zhou; Dengyue Yuan; Fangjun Lin; Hu Chen; Hongwei Wu; Rongbin Wei; Zhiming Xin; Ju Liu; Yundi Gao; Zhiqiong Li (Fish Physiology and Biochemistry, 2014)

Characterization of the immune defense related tissues, cells, and genes in amphioxus - YuShuang Lin; DongYan Chen; Wei Zhang; ZhaoPing Cai; ZhongKe Chen; Ning Zhang; BingYu Mao; HongWei Zhang (Science China Life Sciences, 2011)

Biodegradation of leuco derivatives of triphenylmethane dyes by Sphingomonas sp. CM9 - Jun Wu; Liguan Li; Hongwei Du; Lijuan Jiang; Qiong Zhang; Zhongbo Wei; Xiaolin Wang; Lin Xiao; Liuyan Yang (Biodegradation, 2011)

Grassland responses to grazing: effects of grazing intensity and management system in an Inner Mongolian steppe ecosystem - Philipp Schönbach; Hongwei Wan; Martin Gierus; Yongfei Bai; Katrin Müller; Lijun Lin; Andreas Susenbeth; Friedhelm Taube (Plant and Soil, 2011)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Molecular cloning and characterization of a novel glyoxalase I gene TaGly I in wheat (Triticum aestivum L.) - Fanyun Lin; Jianhong Xu; Jianrong Shi; Hongwei Li; Bin Li (Molecular Biology Reports, 2010)

Bacterioplankton community structure in a eutrophic lake in relation to water chemistry - Jin Zeng; Liuyan Yang; Hongwei Du; Lin Xiao; Lijuan Jiang; Jun Wu; Xiaolin Wang (World Journal of Microbiology and Biotechnology, 2009)

Detection of the end point temperature of thermal denatured protein in fish and chicken meat through SDS-PAGE electrophoresis - Hongwei Gao; Mao Mao; Chengzhu Liang; Chao Lin; Jianhai Xiang (Journal of Ocean University of China, 2009)